2022
DOI: 10.3324/haematol.2021.280444
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional characterization of the CD6-ALCAM T-cell co-stimulatory pathway after allogeneic cell transplantation

Abstract: CD6 is a co-stimulatory receptor expressed on T cells that binds activated leukocyte cell adhesion molecule (ALCAM), expressed on antigen presenting cells, epithelial and endothelial tissues. The CD6-ALCAM pathway plays an integral role in modulating T-cell activation, proliferation, and trafficking. In this study we examined expression of CD6 by reconstituting T cells in 95 patients after allogeneic cell transplantation and evaluated the effects of itolizumab, an anti- CD6 monoclonal antibody, on T-cell activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Compared with control mice, CD6-deficient mice exhibited less severe disease in several murine autoimmune models, including experimental autoimmune encephalomyelitis, psoriasis, and uveitis ( 53 55 ). Consistent with these findings, a humanized anti-CD6 monoclonal antibody, itolizumab, has been shown to be effective for the treatment of psoriasis and rheumatoid arthritis ( 56 , 57 ), owing to its ability to inhibit T-cell activation, proliferation, and production of proinflammatory cytokines ( 58 , 59 ), and is being studied as a therapy for acute graft-vs-host disease ( 60 ). Intriguingly, CD6 is a risk susceptibility gene in IBD ( 61 ), and a higher proportion of CD4 + T cells derived from intestinal tissues from patients with IBD expressed CD6 compared with healthy subsets ( 62 ), indicating that CD6 could represent a potential therapeutic target in IBD.…”
Section: Discussionmentioning
confidence: 82%
“…Compared with control mice, CD6-deficient mice exhibited less severe disease in several murine autoimmune models, including experimental autoimmune encephalomyelitis, psoriasis, and uveitis ( 53 55 ). Consistent with these findings, a humanized anti-CD6 monoclonal antibody, itolizumab, has been shown to be effective for the treatment of psoriasis and rheumatoid arthritis ( 56 , 57 ), owing to its ability to inhibit T-cell activation, proliferation, and production of proinflammatory cytokines ( 58 , 59 ), and is being studied as a therapy for acute graft-vs-host disease ( 60 ). Intriguingly, CD6 is a risk susceptibility gene in IBD ( 61 ), and a higher proportion of CD4 + T cells derived from intestinal tissues from patients with IBD expressed CD6 compared with healthy subsets ( 62 ), indicating that CD6 could represent a potential therapeutic target in IBD.…”
Section: Discussionmentioning
confidence: 82%
“…The glycoprotein known as CD6, which is mostly expressed on the surface of T cells, has received greater attention in the context of immunological disorders. 57 CD6 binding to activated leukocyte cell adhesion molecule (ALCAM) is the most classical signaling pathway, 58 and ALCAM+ perichondrial cells can participate in vascular invasion by recruiting osteoclasts, 59 so CD6 may be associated with osteoclast viability. CD6 transcripts generate multiple CD6 isoforms by alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…The CD6 molecule (CD6_HUMAN, P30203) is a type 1 transmembrane glycoprotein expressed in the cell surface of T cells that binds to ALCAM to function as co-stimulatory molecules and take roles in modulating T-cell proliferation, activation, and trafficking ( Oh et al, 2019 ; Rambaldi et al, 2022 ). A recent study suggested that the anti-CD6 monoclonal antibody, UMCD6, enhanced killing of cancer cells through effects on NK and CD8 + cells ( Ruth et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%